Using Stepwise Reality Check to Analyze Open-end Fund Investors’ Herding Redemption in Taiwan - Wang, Nan Yu; Huang, Chih-Jen; Hsu, Ying-Lin; Huang, Shian-Chang (International Journal of Economics and Financial Issues, 2015)
This study aims to examine whether funds with illiquid assets exhibit stronger sensitivity of redemption outflows to bad past performance than funds with liquid assets. An important aspect of our study is whether large outflows should damage future fund performance in illiquid funds more than in liquid funds. When redeemed in a large scale, the liquidity risk of open-end funds will increase, which in turn leads to a vicious circle between fund redemption and the net asset value decline. Accordingly, Stepwise Reality Check method is taken into account of the financial stability problem and to control for the data-snooping bias. Based on the sample of underperformed mutual funds in Taiwan, the empirical results show that (1) bad past performance in liquid funds is more sensitive on flow-performance relations; (2) The evidence in (1) exists only for institutional-oriented funds, but not for retail-oriented funds; and (3) Illiquid funds damage from a large number redemptions with significant return persistence. The above findings provide valuable references for fund managers to make the plan of their investments. Keywords: Herding redemption; Financial stability; Stepwise Reality Check JEL Classifications: C1; G2; M1